2018
DOI: 10.1002/cbdv.201800289
|View full text |Cite
|
Sign up to set email alerts
|

Novel Podophyllotoxin Derivatives as Potential Tubulin Inhibitors: Design, Synthesis, and Antiproliferative Activity Evaluation

Abstract: A number of podophyllotoxin derivatives (3A-3J) had been designed and synthesized, and their biological activities were evaluated in this study. Moreover, the antiproliferation activities of these compounds against four human cancer cell lines (HepG2, HeLa, A549, and MCF-7) were also tested. The results indicated that the most promising compound 3D displayed potent inhibitory activity over the four human cancer cell lines and was further demonstrated to have potent tubulin polymerization inhibitory effects wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 35 publications
0
8
0
Order By: Relevance
“…Inhibitor of Tubulin PTOX, whose pharmacological effects have been recognized to inhibit microtubule assembly by blocking the colchicine binding site, thereby exhibiting inhibition of microtubule protein polymerization and inducing G2/M blockade, has shown potent antitumor activity (Cortese et al, 1977). PTOX derivatives have also been shown to have the analogous ability (Han et al, 2018). Kamal et al (2011b) synthesized a series of conjugates of 4aza-2,3-didehydropodophyllotoxins Compound 21 (Figure 7), and fluorescent tubulin polymerization analysis showed these PTOX derivatives significantly reduced tubulin units.…”
Section: Main Mechanismmentioning
confidence: 99%
“…Inhibitor of Tubulin PTOX, whose pharmacological effects have been recognized to inhibit microtubule assembly by blocking the colchicine binding site, thereby exhibiting inhibition of microtubule protein polymerization and inducing G2/M blockade, has shown potent antitumor activity (Cortese et al, 1977). PTOX derivatives have also been shown to have the analogous ability (Han et al, 2018). Kamal et al (2011b) synthesized a series of conjugates of 4aza-2,3-didehydropodophyllotoxins Compound 21 (Figure 7), and fluorescent tubulin polymerization analysis showed these PTOX derivatives significantly reduced tubulin units.…”
Section: Main Mechanismmentioning
confidence: 99%
“…Among the 11 compounds that inhibit microtubule assembly, three of them (L1, K1, E2) contained benzodioxole, which has been found in several known microtubule drugs that target colchicin-binding sites [28,29], including polygamain [19], combretastatin A-2 [30], podophyllotoxin [31], steganacin [32] and TUB091/TUB092 [33]. The crystal structure of α /β-tubulin-RB3-tubulin tyrosine ligase (TTL) complex soaked with TUB092 showed that the benzodioxole group positions at the hydrophobic pocket of β-tubulin, a position which is similar to the site that the trimethoxyphenyl moiety (A-ring) of colchicine also occupies [33].…”
Section: Discussionmentioning
confidence: 99%
“…Han and colleagues synthesized several new podophyllotoxin–benzoheterocyclic derivatives ( 114a – j , Figure 14 ) from podophyllotoxin and the corresponding benzoheterocyclic acid following the procedure described above ( Scheme 28 ) [ 154 ]. Among all these derivatives, compound 114d , with an indole moiety, showed the greatest cytotoxicity with IC 50 values of 1.93, 2.20, 5.94, and 10.10 µM against the HepG2, HeLa, A549, and MCF7 tumor cell lines, respectively.…”
Section: C-ring Modifications Of the Podophyllotoxin Skeletonmentioning
confidence: 99%